China’s COVID-19 Humanitarian Response: A Case Study on Indonesia Through Human Security Perspective - Wardhani, Nuke Faridha; Amalia, Ridha; Yapply, Brillin (Global Strategis, 2025)
China’s humanitarian aid during the COVID-19 pandemic highlights the interplay between human security principles and strategic foreign policy. This study examines China’s assistance to Indonesia, a key partner under the Belt and Road Initiative, focusing on the effectiveness, empowerment, and motives behind its actions. Drawing on the human security framework, the article analyzes China’s rapid response through the provision of medical supplies, vaccines, and long-term capacity-building efforts. Key initiatives, such as the Sinovac-Bio Farma vaccine collaboration, illustrate how China integrated immediate relief with long-term cooperation, addressing both health crises and systemic vulnerabilities. The findings emphasize China’s dual motivations namely upholding human security norms and advancing its global position. By leveraging multilateral platforms and bilateral partnerships, China demonstrated its commitment to addressing global health challenges while fostering deeper ties with Indonesia. This case provides valuable lessons for incorporating human security into future foreign aid strategies, underscoring the importance of international cooperation in tackling shared crises. Keywords: Human Security, Humanitarian Aid, COVID-19 Pandemic, Belt and Road Initiative (BRI), Sino-Indonesian Relations Bantuan kemanusiaan Tiongkok ketika pandemi COVID-19 menyoroti keterkaitan antara prinsip keamanan manusia dan kebijakan luar negeri Tiongkok yang strategis. Studi ini mengkaji bantuan kemanusiaan Tiongkok kepada Indonesia yang berfokus pada tiga aspek, yakni efektivitas, pemberdayaan, dan motif, dimana Indonesia merupakan salah satu mitra strategis dalam kerja sama Belt and Road Initiative. Dalam perspektif keamanan manusia, dapat diketahui bagaimana Tiongkok menyediakan bantuan alatalat kesehatan, yakni kerja sama vaksin Sinovac-Bio Farma dan upaya pengembangan kapasitas dalam jangka panjang, merupakan respons yang cepat dalam menghadapi krisis kesehatan dan kerentanan yang sistematik. Temuan tersebut juga menekankan pada motivasi Tiongkok dalam memberikan bantuan kemanusiaan, selain menegakkan norma keamanan manusia juga memajukan kedudukannya dalam skala global. Dengan memanfaatkan kerja sama multilateral dan bilateral, Tiongkok menunjukkan komitmennya untuk mengatasi tantangan kesehatan pada level global sekaligus membina hubungan yang lebih baik dengan Indonesia. Hal ini menjadi menarik ketika menggabungkan perspektif keamanan manusia dalam strategi bantuan luar negeri dengan tetap menekankan pentingnya kerja sama internasional dalam mengatasi krisis bersama. Kata-kata Kunci: Keamanan Manusia, Bantuan Kemanusiaan, Pandemi COVID-19, Belt and Road Inisiatif (BRI), Hubungan Tiongkok-Indonesia